2008
DOI: 10.1002/ajmg.a.32348
|View full text |Cite
|
Sign up to set email alerts
|

Partial growth hormone deficiency and changed bone quality and mass in type I trichorhinophalangeal syndrome

Abstract: The trichorhinophalangeal syndromes (TRPSs) are syndromes due to haploinsufficiency of genes in the chromosome 8q24.12 region. Type I TRPS is characterized by typical facial features including sparse, brittle and fine hair, bulbous nose, and a long philtrum, as well as skeletal abnormalities. Growth retardation is a feature frequently found in these patients, who commonly are of short stature; however, only one case with growth hormone deficiency has been described in a TRPS patient and that patient had type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
(39 reference statements)
1
24
0
2
Order By: Relevance
“…Review of the literature shows that severe osteoporosis is reported in a single patient with TRPS type I, carrying the de novo 1096insA mutation in TRPS1 gene [Shao et al, 2011], while significantly reduced bone mass and quail were described as a new feature of TRPS type I by Stagi et al [2008] and Sarafoglou et al [2010]. Therefore, osteoporosis and alterations of BMD should be considered an additional rare feature of TRPS type I. Interestingly, a single nucleotide polymorphism (rs4355801) mapping on the same chromosomal locus of TRPS1 (8q24.12) has been significantly associated with BMD and osteoporosis by genome-wide association study (GWAS) [Richards et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature shows that severe osteoporosis is reported in a single patient with TRPS type I, carrying the de novo 1096insA mutation in TRPS1 gene [Shao et al, 2011], while significantly reduced bone mass and quail were described as a new feature of TRPS type I by Stagi et al [2008] and Sarafoglou et al [2010]. Therefore, osteoporosis and alterations of BMD should be considered an additional rare feature of TRPS type I. Interestingly, a single nucleotide polymorphism (rs4355801) mapping on the same chromosomal locus of TRPS1 (8q24.12) has been significantly associated with BMD and osteoporosis by genome-wide association study (GWAS) [Richards et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Stagi et al [13] described 2 GH-responsive patients with TRPS I who had normal GH responses to provocative testing [13]. The authors however considered the patients to both have partial growth hormone deficiency based on low nocturnal mean GH concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Naselli et al and Sohn et al reported failure of GH treatment in a pair of monozygotic twins and 2 other unrelated patients with TRPS I [11,12], whereas Stagi et al and Sarafoglou et al reported that GH treatment was effective in improving height velocity in 4 patients with TRPS I [13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Kısa boy bu hastaların diğer bir karakteristik özelliğidir 3 . Eklemlerde pertes benzeri değişiklikler görülür 1,8 . Kısa boy bu olgularda bildirilen yaygın bir özellik olmakla birlikte son bildirilerde TRFS tip 1'de kısa boy ile birlikte gecikmiş kemik yaşı, azalmış kemik mineral dansitesi ve parsiyel büyüme hormonu (GH) eksikliği bulunan olgular gösterilmiştir.…”
Section: Discussionunclassified
“…Kısa boy bu olgularda bildirilen yaygın bir özellik olmakla birlikte son bildirilerde TRFS tip 1'de kısa boy ile birlikte gecikmiş kemik yaşı, azalmış kemik mineral dansitesi ve parsiyel büyüme hormonu (GH) eksikliği bulunan olgular gösterilmiştir. Olguların GH replasmanı ile başarılı bir şekilde tedavi edildiği bildirilmiştir 6,8 . Olgumuzda flankslarda koni şeklinde epifiz saptanmış olup, boy sınır persantildeydi (SD:-2,2), IGF1 normal sınırlarda, kemik yaşı ise normal sınırların altındaydı.…”
Section: Discussionunclassified